👤

1. P (6,3)
2. P (11,2)​


Sagot :

[tex] \large\sf{PERMUTATION} [/tex]

_ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _

[tex]\quad\quad\quad\quad\quad\large\sf{(1) \: 120}[/tex]

[tex]\quad\quad\quad\quad\quad\large\sf{(2) \: 110}[/tex]

_ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _

SOLUTION

P (6,3)

  • ➝ P(6,3) = n!/(n - r)!
  • ➝ p(6,3) = 6!/(6 - 3)!
  • ➝ p(6,3) = 6!/(3)!
  • ➝ p(6,3) = 6 x 5 x 4 x 3!/3!
  • ➝ p(6,3) = 120

Therefore the answer is 120

_ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _

SOLUTION

P (11,2)

  • ➝ 11^P2 = 11!/(11 - 2)!
  • ➝ 11^P2 = 11!/9!
  • ➝ 11^P = 11 - 10 - 9!/9!
  • ➝ 11^P2 = 11 • 10
  • ➝ 11^P2 = 110

Therefore, the answer is 110

_ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _

#CarryOnLearning

[tex] \large\sf{DIRECTIONS:} [/tex]

[tex]\quad\quad\quad\quad\quad\sf{(1) \: 120}[/tex]

[tex]\quad\quad\quad\quad\quad\sf{(2) \: 110}[/tex]

_ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _

SOLUTION

P (6,3)

  • ➝ P(6,3) = n!/(n - r)!
  • ➝ p(6,3) = 6!/(6 - 3)!
  • ➝ p(6,3) = 6!/(3)!
  • ➝ p(6,3) = 6 x 5 x 4 x 3!/3!
  • ➝ p(6,3) = 120

Therefore the answer is 120

_ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _

SOLUTION

P(11,2)

  • ➝ 11^P2 = 11!/(11 - 2)!
  • ➝ 11^P2 = 11!/9!
  • ➝ 11^P = 11 - 10 - 9!/9!
  • ➝ 11^P2 = 11 • 10
  • ➝ 11^P2 = 110

Therefore, the answer is 110

_ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _

#CarryOnLearning